2018
DOI: 10.1002/jssc.201800656
|View full text |Cite
|
Sign up to set email alerts
|

Recent development trends for chiral stationary phases based on chitosan derivatives, cyclofructan derivatives and chiral porous materials in high performance liquid chromatography

Abstract: The separation of enantiomers by chromatographic methods, such as gas chromatography, high-performance liquid chromatography and capillary electrochromatography, has become an increasingly significant challenge over the past few decades due to the demand of pharmaceutical, agrochemical, and food analysis. Among these chromatographic resolution methods, high-performance liquid chromatography based on chiral stationary phases has become the most popular and effective method used for the analytical and preparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 121 publications
(190 reference statements)
0
31
0
Order By: Relevance
“…Several reviews have assembled the advances on preparation and evaluation of this type of CSPs over the years [43,45,49,50,51,52,57,58,59,80,85,86,87,88,89,90,91,92,93]. Nevertheless, this research field is always evolving being the most recent polysaccharide-based CSPs presented on Table S1 (supplementary material).…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have assembled the advances on preparation and evaluation of this type of CSPs over the years [43,45,49,50,51,52,57,58,59,80,85,86,87,88,89,90,91,92,93]. Nevertheless, this research field is always evolving being the most recent polysaccharide-based CSPs presented on Table S1 (supplementary material).…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 99%
“…Moreover, they can be used in different elution modes [239]. Although cyclofructan-based CSPs are recent, some reviews can be found related to its developments and applications [45,55,85,87,88,90]. The elucidation of their chiral recognition mechanisms has been the focus of some studies to clarify the interactions between the CSP and the analytes [45].…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 99%
“…Enantiomeric separation, a significant aspect in pharmaceutical analysis, have drawn great attention in the past few decades. This interest mainly due to the fact that the enantiomers of racemic drugs usually exhibit different physiological activities as well as even opposite pharmacokinetic and pharmacodynamic effects in body [1,2]. Among the various approaches, CE has been considered as a favorable technique for enantioseparation in recent years because of its unique advantages such as flexibility in condition, high speed, high efficiency, and small amount of sample [3].…”
Section: Introductionmentioning
confidence: 99%
“…In pharmaceutical applications, enhancing the water stability, mechanical strength, and biocompatibility of MOFs while maintaining their other advantages remains a big challenge [23][24][25]. To solve this problem, researchers have attempted to fabricate MOF nanocomposites with other materials, such as polymers, silica, graphene, or carbon nanotubes, which have different properties, as the reinforcement phase [26][27][28][29][30][31][32][33][34][35][36][37][38]. Silica is suitable for preparation of composite materials to improve the performance of MOFs due to its high stability and structural adjustability [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%